PEMBUATAN GULA DAN ALKOHOL DARI BEBERAPA JENIS KAYU - Gusmailina Gusmailina; Hartoyo Hartoyo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
This article describes the experiment of sugar and alcohol contents from 3 wood species, i.e. jelutung (Dyera costulata, Hook. F), keruing (Dipterocarpus appendiculatus, Sheff) and durian (Durio excelsus, Bakb) by using hydrolysis and fermentation process. Treatment condition for hydrolysis were at 3 levels of sulfuric acid concentration which were 1%, 2%, and 3% respectively. The fermentation methods agent for producing alcohol from sugar of wood hydrolysis was the yeast of bread containing Saccharomyces cereviceae.The result of this experiment indicated that the yield of sugar ranges from 9.71 % - 11.89% with average of 1,06%. This average yield of sugar falls in the range of the sugar yield obtained from other researches which have range from 11-18%. The average alcohol yield obtained from sugar fermentation was 2.62%. This yield was lower compared with other experiment producing alcohol from wood abroad, i.e. 8 - 15%. The result showed that the yield of sugar is not affected by the wood species and low concentration of sulfuric acid treatment.